2000
DOI: 10.1086/315456
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 8 in Brazilian Amerindians: A Hyperendemic Population with a New Subtype

Abstract: Human herpesvirus 8 (HHV-8) epidemiology in Brazilian Amerindians was studied. Use of an immunofluorescence (IFA) test for latent antibody demonstrated that the prevalence of HHV-8 in 781 Amerindians of diverse tribes (overall, 53% prevalence) was not related to language group or sex but rather increased gradually from 41% in children <10 years of age to 65% in adults >/=30 years of age. In IFA-positive subjects, HHV-8 DNA was detected in 3 (16%) of 19 mononuclear cell samples from peripheral blood and in 1 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
159
4
50

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 180 publications
(223 citation statements)
references
References 36 publications
10
159
4
50
Order By: Relevance
“…An increase in HHV-8 seroprevalence with age suggests that, new infection occurs during adulthood [18], and this finding was also detected in Brazil [2,5].…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…An increase in HHV-8 seroprevalence with age suggests that, new infection occurs during adulthood [18], and this finding was also detected in Brazil [2,5].…”
Section: Resultsmentioning
confidence: 60%
“…Studies regarding its presence in Brazil disclosed HHV-8 endemic populations among Amerindians and homosexual/bisexual men infected with HIV-1 [2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…So far four subtypes (A, B, C, and D) and at least 13 distinct variants were identified on the basis of sequence heterogeneity. More recently, it was found that a novel subtype (subtype E), closest to the D subtype, was circulating in an isolated population of the Brazilian Amerindians [Biggar et al, 2000]. Subtypes A, B, and C correspond to those of the initial classification based on the ORF 26 gene heterogeneity .…”
Section: Introductionmentioning
confidence: 87%
“…KSHV infection has also been described in cases of haemophagocytic syndrome (HPS) but is not the only viral cause of this condition [15][16][17]. association with certain human populations can still be seen for clades B, D, and E, which are found primarily in people of African descent, old Asian and Polynesian populations, and Amerindian populations, respectively [30][31][32][33][34][35]. With the exception of a branch of clade A, A5, which is also frequently found in Africa [30,32], clades A and C are now found in northern Europe, the Americas, and Asia without any clear-cut association with defined populations, presumably as a result of the extensive mixing of European populations during the history of human migration.…”
Section: History and Involvement In Diseasementioning
confidence: 99%
“…However, one viral gene, K1, located at the 'left' end of the viral genome in the orientation shown in Figure 1, contains hypervariable regions with up to 40% protein sequence divergence between different clades [30][31][32][33][34][35]. Remarkably, the protein sequence in these hypervariable regions seems to have evolved as a result of some selective pressure [30,31,35].…”
Section: History and Involvement In Diseasementioning
confidence: 99%